A numerical method based on explicit finite difference for solving fractional hyperbolic PDE’s - Saeed, Abdulkafi (International Journal of Applied Mathematical Research, 2016)
In this paper, a new numerical scheme based on explicit finite difference approximation for solving fractional hyperbolic partial differential equations (FHPDE’s) is formulated. Numerical studies for the model problems are presented to confirm the accuracy and the effectiveness of the proposed method. The obtained results of proposed system are compared with exact solutions and the original system to show the efficient of the new method.